The impact of consultants’ power dynamics on clients’ self-efficacy and managerial stress - Rotem Lachmi; Batia Ben-Hador; Yael Brender-Ilan (Frontiers in Psychology)
Power bases in management are crucial for leaders to effectively influence their teams and achieve organizational goals. Management consultants leverage various power bases, particularly Expert and Referent power, to influence client organizations and drive change. While previous studies have examined factors distinguishing successful consultants and the power they need to motivate clients, they focused solely on consultants’ perspectives. This study investigates the relationship between consultants’ power bases (principally Expert and Referent) and clients’ self-efficacy and managerial stress. The aim is to determine how consultants’ use of their power base affects clients’ experience and outcomes. One hundred clients participated in a study testing the correlation between consultants’ power bases and clients’ self-efficacy and stress management. Using moderation statistical models, a significant correlation was found between consultants’ Expert power and clients’ self-efficacy, with managerial stress moderating this relationship. Consulting success is measured by the extent to which it enhances clients’ self-efficacy, enabling them to effectively achieve their organizational goals and overcome challenges. The results show that Expert power is crucial in boosting clients’ self-efficacy, except under conditions of high managerial stress. This study contributes to the literature by highlighting a key power base and offering new insights into power dynamics in management consulting. Additionally, it provides practical benefits for enhancing consulting outcomes, influencing both client and consultant perspectives, and potentially improving the overall effectiveness of management consulting engagements.